CURRENT PRINCIPLES OF NON-INVASIVE TREATMENT OF DENTIN HYPERSENSITIVITY (PART 2) - O.V. Hurzhii; T.P. Skrypnikova; O.O. Kulai; T.A. Khmil; Yu.V. Tymoshenko; S.V. Prykhodchenko; V.O. Dubyna (Український стоматологічний альманах)
The study of dental status has shown that over the past 20 years, visits related to dentin hypersensitivity (DH) in Western European countries have increased by 35%, and in the USA by 42%. The prevalence of DH varies widely across the world, from 20.6% in India to 41.9% in China, affecting more women than men, and more young people than the elderly. Among patients with periodontal diseases, dentin sensitivity occurs in 61–98% of cases. Research conducted in the United Kingdom and Jordan confirmed that the prevalence of DH is particularly high in patients with periodontal diseases, and is facilitated by excessive tooth brushing, tartar removal, root planing and wear due to parafunctional habits. Studies in Germany emphasized that the treatment of DH should not be underestimated, as the pain caused by DH significantly reduces patients’ quality of life.